PENGHAPUSAN DISKRIMINASI TERHADAP PEREMPUAN DALAM BIDANG PERKAWINAN MENURUT HAM DAN HUKUM PERKAWINAN ISLAM DI INDONESIA - Nurhasanah Nurhasanah (Universitas Islam Negeri Imam Bonjol Padang, 2012)
As a participating member of the United Nations approved the Universal Declaration, Indonesia also ratified the provisions of the Declaration of Human Rights and the Convention On The Elimination Off All Forms of Discrimination Against Women with the enactment of Law No. 7 of 1984. One of the conditions set forth in it is the elimination of discrimination against women in the field of marriage. Furthermore, the Indonesian government also has an obligation to implement the contents of the declaration in its laws and regulations. This means that Indonesia implement the provisions of legislation in the field of marriage law in Indonesia that are relevant to the content of the convention. One positive effect of marriage law in Indonesia is an Islamic marriage laws apply to Muslims in Indonesia who are the majority of Indonesia's population. Keywords : Human Rights, Elimination of Discrimination Against Women, Islamic Law in IndonesiaCopyright © 2012 by Kafa`ah All right reservedDOI : 10.15548/jk.v2i1.50